El hombre es un hombre para el hombre (2010)
ABSTRACT: The aim of this article is to show that aggressiveness and some cruel and violent actions are part of the drive condition in human beings. They are neither historical contingencies nor ideological effects. From different philosophical points of view, cruelty is presented as a deviation of human nature. Freud places cruelty at the center of human drives. The idea is to acknowledge this and avoid denial, which helps to keep repetition as a return of the repressed.